2018
DOI: 10.2147/ijnrd.s184671
|View full text |Cite
|
Sign up to set email alerts
|

Self-management and associated factors among patients with end-stage renal disease undergoing hemodialysis at health facilities in Addis Ababa, Ethiopia

Abstract: IntroductionPatients with end-stage renal disease (ESRD) face multifaceted problems arising from complications of the disease and dialysis that require consistent and, effective self-management from the patients’ side, on top of the management offered by health care professionals. However, little is known about the level of self-management and influencing factors among patients with ESRD undergoing hemodialysis in the study area. Therefore, the aim of this study was to assess self-management and associated fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 29 publications
3
26
1
2
Order By: Relevance
“…A higher education level is usually associated with greater knowledge. Knowledge in general has a major impact on self-management, self-efficacy, and the foundations of decision making [ 3 , 10 , 29 ]. Illness-specific knowledge is also significantly positively correlated with self-management and self-efficacy [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A higher education level is usually associated with greater knowledge. Knowledge in general has a major impact on self-management, self-efficacy, and the foundations of decision making [ 3 , 10 , 29 ]. Illness-specific knowledge is also significantly positively correlated with self-management and self-efficacy [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding agrees with previous studies demonstrating that self-efficacy has a significant and reciprocal influence on overall self-management [ 3 , 7 , 11 , 19 , 25 , 29 , 30 , 31 ]. Patients with a high level of self-efficacy have better self-management, especially in the category of self-care [ 3 , 10 ]. Self-efficacy can help the patient to engage in self-management behaviours and vice versa [ 3 , 7 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar study in Ethiopia reported statistically significant positive associations between self-management and education. 23 In addition, our study demonstrated that underweight patients (BMI <18.5) are 1.6 times more likely to develop CHF than those who have normal weight . This finding is in line with a systematic review in Asia, 24 the USA 25,26 , Sweden 25 and Germany.…”
Section: Discussionmentioning
confidence: 53%